Design of Truncated Hyperboloid Solar Concentrator by Using Zemax Program - Hamza, Hassanein Nouri; Badr Hasan, Alaa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
A hyperboloid solar concentrator (HSC) was designed with a truncation angle side to the entrance aperture by simulation in the Zemax Optical Design software. The (HSC) has a wide exposure range to solar radiation due to the relatively large entrance aperture. The design consists of an entrance aperture facing the sun to obtain the largest possible amount of solar radiation, and a small exit aperture compared to the entrance aperture whose mission is to receive solar radiation after it enters the entrance aperture and reflects it from the inner reflective walls of the (HSC). In the exit aperture, there is a detector to measure the number of rays incident on it, which is a measure of the optical efficiency of the sample. A hybrid sample has been designed with an angular truncation at the front of it. This feature contributes to a greater absorption of solar radiation for greater efficiency. The results showed a slight change in the value of optical efficiency when changing the truncation angle, and the values of optical efficiency were superior to designs that had a small concentration ratio, and optical efficiency increased with increasing the concentrator length.